2015
DOI: 10.1007/s10973-015-4843-2
|View full text |Cite
|
Sign up to set email alerts
|

Thermal analysis and adiabatic calorimetry for early-age concrete members

Abstract: This paper describes a procedure for thermal analysis on early-age concrete structures with experimentally obtained concrete adiabatic temperature rise and interface conductance between steel formwork and concrete. During hydration, concrete is considered in the analysis as non-homogeneous and the degree of hydration is dependent on both thermal loading and thermal properties development. A thermal convection model was implemented to simulate the external heat loss. Experimentally, two 1.2-m concrete cubes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 12 publications
1
16
0
3
Order By: Relevance
“…Nghiên cứu của Schutter [6] chỉ ra rằng cường độ chịu nén tuổi sớm của bê tông thường có mối quan hệ tuyến tính với mức độ thủy hóa (). Sự tương quan tuyến tính cũng được kiểm chứng và khẳng định bởi nghiên cứu của Lin và Chen [15]. Tuy nhiên, đối với hỗn hợp bê tông cường độ cao có sử dụng hàm lượng chất kết dính và phụ gia siêu dẻo lớn thì chưa chắc hai đại lượng này có mối tương quan chặt như đối với hỗn hợp bê tông thường.…”
Section: Thảo Luận Về Mối Quan Hệ Giữa Mức độ Thủy Hóa Và Cường độunclassified
“…Nghiên cứu của Schutter [6] chỉ ra rằng cường độ chịu nén tuổi sớm của bê tông thường có mối quan hệ tuyến tính với mức độ thủy hóa (). Sự tương quan tuyến tính cũng được kiểm chứng và khẳng định bởi nghiên cứu của Lin và Chen [15]. Tuy nhiên, đối với hỗn hợp bê tông cường độ cao có sử dụng hàm lượng chất kết dính và phụ gia siêu dẻo lớn thì chưa chắc hai đại lượng này có mối tương quan chặt như đối với hỗn hợp bê tông thường.…”
Section: Thảo Luận Về Mối Quan Hệ Giữa Mức độ Thủy Hóa Và Cường độunclassified
“…They found that the PCA and ACI 207.R methods provided poor predictions. More recently, finite-element and finite-difference have been used to predict the temperature development of mass concrete structures by modeling the heat generation measured in adiabatic or isothermal conditions [2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The method developed can be used to estimate the thermallyinduced stress of concrete members so that precautions can be implemented prior to concrete cast in order to prevent unexpected cracking. The FEM stress analysis procedures were published in Lin and Chen (2015).…”
Section: Stress Analysis and Resultsmentioning
confidence: 99%
“…The hydration parameters, τ and β, were two constants depending on the mix design. τ = 14.0 and β = 0.94 were determined from the adiabatic temperature rise tests and curve fitting method as described in Section 5.2.2 and a published research paper by Lin and Chen (2015). were tested using the 15 cm × 30 cm (6 in × 12 in) cylinders and 10 cm × 20 cm (4 in × 8 in)…”
Section: Mechanical Properties Of Early Age Concretementioning
confidence: 99%
See 1 more Smart Citation